Antioxidative phenolic compounds from the aerial parts of Cyperus exaltatus var. iwasakii and their HPLC analysis - Jungwon Choi; Hak-Dong Lee; Hyejin Cho; Chang-Dae Lee; Gia Han Tran; Hoon Kim; Sung-Kwon Moon; Sanghyun Lee (Applied Biological Chemistry, 2023)
Abstract The constituents and antioxidant activities of Cyperus exaltatus var. iwasakii (CE) have not been studied to date. In this study, the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6 sulfonic acid) (ABTS) assays were used to evaluate the radical-scavenging activities of the ethanol extract, four fractions, and isolated compounds of CE. In addition, phenolic acids and flavonoids were isolated from the ethanol extract of CE using column chromatography. The compounds identified by spectroscopy were gallic acid, protocatechuic acid, vanillic acid, p-coumaric acid, rutin, ferulic acid, isoquercitrin, astragalin, quercetin, luteolin, apigenin, tricin, and kaempferol. Quantitative analysis using high-performance liquid chromatography (HPLC) revealed that the major flavonoids of CE were astragalin and tricin and that the major phenolic acid was p-coumaric acid. In addition, comparative analysis of CE from Ganghwa and Hampyeong habitats using HPLC showed that the Hampyeong CE had a higher phytochemical content. Comparative analyses of the isolated compounds were also conducted among five Cyperus species. The highest antioxidant activities were found in the ethyl acetate (EtOAc) fraction, and among the compounds isolated from CE, vanillic acid and quercetin showed remarkable antioxidant activity even when compared with ascorbic acid. The results demonstrate the usefulness of CE, which has not been sufficiently studied previously, and will facilitate the evaluation of its potential effectiveness as antioxidant functional plant material.